Ethnic Issues in Tony Hillerman's Detective Novels - Bohatová, Andrea (Univerzita Pardubice, 2017)
The bachelor thesis deals with Tony Hillerman's detective novels, particularly how ethnic issues are depicted in chosen novels. The thesis characterizes Hillerman's work and sets it into the historical and literal context and the term ethnicity is defined. The means by which Hillerman depicts the ethnicity in the novels are divided into several sections and analyzed. The paper also describes how Hillerman is assessed by experts and readers.
Etnické aspekty detektivních románů Tonyho Hillermana
Keywords: ethnicity; Navajos; crime fiction; detective novels; Native Americans; etnicita; Navahové; detektivka; detektivní romány; severoameričtí Indiáni